2019
DOI: 10.1177/0256090919898909
|View full text |Cite
|
Sign up to set email alerts
|

Financial Modelling for Business Sustainability: A Study of Business Correspondent Model of Financial Inclusion in India

Abstract: Executive Summary The study highlights the need for measures to accelerate the pace of the business correspondent (BC) model for financial inclusion in India. The financial analysis of the existing BCs with the existing products and services in practice shows a very diffusive break-even (more than 7 years). The occurrence of such a long-term break-even point can be a potential threat to the sustainability of new and struggling entrepreneurs like a Customer Service Point (CSP). A CSP agent runs a kiosk of a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In the year 2006, the RBI devised the business correspondent (BC) model to reach financial services into the hinterland, across populations belonging to different economic strata. The BC model deploys BCs or bank mitras ( mitra stands for friend in Hindi) that work as multiple customer service points (CSP), to deliver doorstep banking to the millions of unbanked Indians (Uzma and Pratihari 2019 ). The Bank Mitras are responsible for delivering financial services like transfer of money, opening of a bank account, facilitating withdrawal and deposits on a commission basis (Ujjawal et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the year 2006, the RBI devised the business correspondent (BC) model to reach financial services into the hinterland, across populations belonging to different economic strata. The BC model deploys BCs or bank mitras ( mitra stands for friend in Hindi) that work as multiple customer service points (CSP), to deliver doorstep banking to the millions of unbanked Indians (Uzma and Pratihari 2019 ). The Bank Mitras are responsible for delivering financial services like transfer of money, opening of a bank account, facilitating withdrawal and deposits on a commission basis (Ujjawal et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…They published reports on the performance of the BC-Model conveying lack of transparency of information and coordination among BC agency and BCs as impediments to the success of the BC-Model. Considering one of the strategic goals of the model is to be sustainable (Uzma & Pratihari, 2019), this was added as a measure under the strategic dimension. Review of consultancy reports (IFMR, 2013;Kumari et al, 2014;MicroSave, 2014) indicated issues regarding transparency of information among the stakeholders as well as lack of cooperation and co-ordination hampering satisfaction of stakeholders thereby impeding progress of the model.…”
Section: Satisfactionmentioning
confidence: 99%
“…However, 48% of these bank accounts have seen no transactions since being opened. Furthermore, additional studies indicate that the BC-Model is not performing in an optimal manner (Mehrotra et al, 2018;Uzma & Pratihari, 2019). There is a growing need to understand the facets contributing to the success of the BC-Model (Uzma & Pratihari, 2019).…”
Section: Introducing the Business Correspondence Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The role played by bank branches can be replaced by the Business Correspondent (BCs). The role of BC is to perform the banking services on behalf of banks, such as cash services, opening bank accounts using mobile, issuing small amounts of credits (Uzma et al, 2019). However, the critical challenge to successfully implement this concept lies in identity creation, verification, and entitlement establishment of the person to open/ enable mobile-enabled savings account (Chopra et al, 2013b).…”
Section: Innovative Services and Financial Inclusion In Developing Co...mentioning
confidence: 99%